الفوائد الـحِسَانُ في مصطلح الحديث للشَّيخ محمَّدِ بن عبد العالي الـجَعْفَريِّ البُوْتِيْجيِّ من علماء القرن الحاديَ عشَرَ دراسةً وتحقيقًا: A Study of al-Fawā’id al-Ḥisān fī Muṣṭalaḥ al-Ḥadīth by al-Shaykh Muḥammad b. ‘Abd al-‘Ālī al-Ja‘farī al-Būtījī - فيصلُ بن سيِّدٍ محمَّدِ بن حَـمِيدٍ القَلَّافُ (الدراسات الإسلامية, 2023)
This article studies the manuscript titled al-Fawā’id al-Ḥisān fī Muṣṭalaḥ al-Ḥadīth by Abdul Aali al-Jafari albutiji. The manuscript relates to the discipline of Ḥadīth and its sciences, and it is preserved by the Süleymaniye Library in Istanbul. The science of Ḥadīth provides criteria and methods for distinguishing authentic Prophetic traditions from weak ones. The author of this manuscript was a prominent Muslim scholar of the eleventh century and his academic work has been acknowledged and highly appreciated by later scholars. However, this booklet has remained unpublishable. This paper studied this book so that it could be brought to public view and scholars and students could benefit from it.